Legal Consequences of Making a Notary's Cover Note in the Implementation of Notary's Duties - Lubis, Ikhsan; Murwadji, Tarsisius; Sunarmi, Sunarmi; Sukarja, Detania (SASI, 2023)
Introduction: One of the legal goods provided by a notary is a cover note, which is a statement in the management of a deed or a notarial document stating that the deed is in progress and can be finished within the time set by the cover note.Purposes of the Research:  A notary certificate is referred to as a cover note, as a substitute for the process of obtaining a certificate from a notary public, land title guarantees can be replaced temporarily depending on needs and developments. Notaries can make issue cover notes, which have legal consequences and make legal norms null and void. The legal basis for making and issuing cover notes is not yet known. This paper discusses two matters: What legal authority does a notary have to issue a cover note? What are the legal consequences of publishing a cover note by a notary? Methods of the Research: This is typical of legal writings that take a legal approach and examine legal concepts. In socio legal research, research begins with a hypothesis. After formulating the hypotheses, the hypotheses are tested. Data collection techniques in socio legal research are carried out through interviews, observation, questionnaires and document analysis.Results of the Research: However, notaries are allowed to issue and make cover notes because it is a form of agreement. This paper concludes that there is no legal basis for regulating cover notes. If the duties and authorities do not comply with the contents of the cover note, the law will result in a violation of Article 1366 of the Criminal Code.